Witchcraft, Oracles and Magic among the Azande - Evans-Pritchard, Edward E. (Clarendon Press, 1976)
Given unquestioned premises, Azande ideas of witchcraft, oracles, and magic are consistently logical and practical. Their beliefs have nothing to do with “the supernatural,” since for them there was only one “world”—that of everyday experience.
free